2015
DOI: 10.1080/14786419.2015.1095748
|View full text |Cite
|
Sign up to set email alerts
|

Development of minimal fermentation media supplementation for ethanol production using twoSaccharomyces cerevisiaestrains

Abstract: 26Ethanol production by fermentation is strongly dependent on media composition. Specific 27 nutrients, such as trace elements, vitamins and nitrogen will affect the physiological state and, 28consequently, the fermentation performance of the microorganism employed. 29The purpose of this study has been to assess the highest ethanol production by a minimal 30 medium, instead of the more complex nutrients supplementation used during alcoholic 31 fermentation. All fermentation tests were carried out using a micro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 36 publications
0
14
0
2
Order By: Relevance
“…According to Anupama and Ravindra [34], fermented products containing SCP can feed both humans and animals, thereby replacing expensive conventional sources of protein such as fishmeal and soymeal. However, it is important to use a microorganism that are "generally regarded as safe (GRAS)" for fermentation in order to promote its use [35][36][37][38][39]. The yeast Saccharomyces cerevisiae is widely accepted, considering its use in traditional fermentation and its nutritional quality [22].…”
Section: Introductionmentioning
confidence: 99%
“…According to Anupama and Ravindra [34], fermented products containing SCP can feed both humans and animals, thereby replacing expensive conventional sources of protein such as fishmeal and soymeal. However, it is important to use a microorganism that are "generally regarded as safe (GRAS)" for fermentation in order to promote its use [35][36][37][38][39]. The yeast Saccharomyces cerevisiae is widely accepted, considering its use in traditional fermentation and its nutritional quality [22].…”
Section: Introductionmentioning
confidence: 99%
“…Among the microorganisms applied, yeasts have also been used as inoculum, along with lactic bacteria, to ferment fish waste [19] for converting it to a useful product that can be used as an ingredient to balance the food rations of animals. Yeast has many different immunostimulatory compounds, e.g., nucleic acid, b-glucans, and mannan oligosaccharides [20,21]. These compounds may enhance the growth of different fish species and therefore can be considered as the best health promoters for fish culture [22].…”
Section: Introductionmentioning
confidence: 99%
“…[54] Furthermore, Tropea [55] studied the ethanol production by two S. cerevisiae strains with three different nitrogen sources cheaper than yeast extract. The study showed that the ethanol production elevated to 2.29% and 2.34% for both S. cerevisiae strains.…”
Section: Ethanol Production During Different Fermentation Periods At mentioning
confidence: 99%